Gametogenesis and reproduction of the matrinxã Brycon orthotaenia (Günther, 1864) (Pisces: Characidae) in the São Francisco river, Minas Gerais, Brazil - T. L. Gonçalves (Brazilian Journal of Biology)
The gametogenesis and reproduction of the matrinxã, Brycon orthotaenia in the São Francisco river, Pirapora Region, Minas Gerais, were studied from December, 1998 to November, 1999. The matrinxã B. orthotaenia is an endemic species in the São Francisco river basin in Brazil and important for commercial fishing. The size of the 1st gonadal maturation, indicated by the total length of the smallest spent males and spawned female, was 32.0 and 40.5 cm respectively. Reproduction occurred from October to January, when high frequencies of females and males at an advanced ripening/mature stage and spawned females were found. The short spawning period and histological characteristics of spawned ovaries containing only oocytes in stages of initial development, along with post-ovulatory and atresic follicles, indicated that Brycon orthotaenia presents total spawning.